Power supply for a plasma emitter.; Instruments and experimental techniques; Vol. 23, № 2 - Koval N. N. Nikolay Nikolaevich (1980, 1980)
The basic circuit of a supply unit intended for pulse excitation of the arc discharge with a frequency of 5-50 Hz in electron accelerators with plasma emitters is described. The supply unit consists of a firing supply and a main supply. The firing supply is designed to fire the discharge and constitutes a generator of high-voltage pulses with an amplitude of 6 kV and low duration (1.5 µs). The main supply made as a low-voltage artificial forming line shapes a required discharge current pulse with an amplitude of 10-40 A and duration of 100 µs and is connected to discharge gap after firing the discharge. The circuit has been tested in a diode electron accelerator. At an accelerating voltage of 250 kV and a discharge current of 30 A the beam current constitutes 15 A. The pulsed supply of the discharge provides modulation of the electron beam current at a constant accelerating voltage. A conclusion has beeen drawn that employment of the described circuit makes it possible to increase the supply unit efficiency 10 times